Why do men often not use condoms in their relationships with casual sexual partners in Uganda - Rutakumwa, Rwamahe; Mbonye, Martin; Kiwanuka, Thadeus; Bagiire, Daniel; Seeley, Janet (Culture, health & sexuality, 2015)
With a focus on Uganda, this paper examines men’s condom use in sexual relationships with casual partners and what this might tell us about men’s vulnerability to HIV-infection. We carried out repeat interviews with 31 men attending a clinic serving women at high risk for HIV infection and their partners in Kampala. We found that the experience of condom-less sex in the men’s youth, itself the outcome of a restrictive home-environment, was perceived as influencing later unsafe sexual behaviour. Peer pressure encouraged men to have multiple partners. Alcohol negatively affected condom use. Men often opted not to use a condom with women they thought looked healthy, particularly if they had had sex with the woman before. Some men who were HIV-positive said they saw little point in using condoms since they were already infected. A concerted effort is required to reach men, like those in our study, to halt HIV and the transmission of other sexually transmitted infections.
Keywords: condoms; HIV prevention; Sex; Relationships; Uganda